Driving errors influence an older drivers decision to give up or restrict driving. (1st March 2011) - Keay, L; Munoz, B; Turano, K; Munro, C; Duncan, D D; Baldwin, K; Bandeen-Roche, K J; Gower, E W; West, S K
Abstract : Purpose: Explore driving errors in older drivers and the subsequent decision to restrict or stop driving. Methods: 1425 drivers aged 67–87, enrolled in a longitudinal study completed 5-day naturalistic driving assessment. Rate of failure to stop at red traffic lights, stop signs or safely execute left turns were modelled as predictors of stopping or restricting driving. Results: 1237 (87%) completed 12-months, excluding those already restricting driving(n=35), 1.5% (18/1202) had stopped and 3.4% (41/1202) restricted their driving. Errors were observed in 32/1171 (2.7%) participants at red lights, 75/1155 (6.5%) at stop-signs, 88/1170 (7.5%) at left turns. The average failure rate per traffic light, stop sign and left turn was 0.2%, 2.2% and 0.4%, respectively. Police stopped 182 drivers during the year (15%), 81 were issued infringement notices (7%) and 34 were advised to stop or restrict driving (3%) however these factors were not predictive of incident driving change. Those with traffic light failures were more likely to stop or restrict their driving (adjusted OR 1.295; 95% CI 1.078 to 1.555 per per cent increase in failure rate). Failed stop sign (p=0.6) and left turns (p=0.4) were not predictive. Conclusions: Driving errors were measured objectively in a large cohort of older drivers. While a rare event, red traffic light errors increased likelihood of subsequently restricting or ceasing driving. These findings lend support for self-regulation of driving exposure.